2012
DOI: 10.1071/an11146
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and survival of Chinese Holstein dairy cows in central China

Abstract: Fertility and longevity, major factors affecting the economic performance of dairy herds, are influenced by management and genetics. This study determined the reproductive performance and survival of Chinese Holstein cows in a large, modern dairy farm in central China using two complementary datasets. In Dataset 1, fertility and culling records were obtained from 1430 cows calving in 2008; in Dataset 2, all calving episodes during 2005 and 2006 were recorded (n = 1540) and the subsequent survival and reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
1
19
2
1
Order By: Relevance
“…An Italian study identified a mean AFC at 28.1 months of age (Pirlo et al, 2000) taken from a large heifer data set, but this data set excluded all heifers calving <20 and >36 months of age and therefore excluded older heifers. Other studies have also reported different average AFCs across the world (Ettema and Santos, 2004;Bach, 2011;Wu et al, 2012) and these studies have been based on either single or a few farms, limiting the exposure to different management systems and geographical regions. The present study represents one of the largest study to date, but it remains uncertain as to whether this truly reflects the UK situation, because a convenience sample was used to ensure data of sufficient quality.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian study identified a mean AFC at 28.1 months of age (Pirlo et al, 2000) taken from a large heifer data set, but this data set excluded all heifers calving <20 and >36 months of age and therefore excluded older heifers. Other studies have also reported different average AFCs across the world (Ettema and Santos, 2004;Bach, 2011;Wu et al, 2012) and these studies have been based on either single or a few farms, limiting the exposure to different management systems and geographical regions. The present study represents one of the largest study to date, but it remains uncertain as to whether this truly reflects the UK situation, because a convenience sample was used to ensure data of sufficient quality.…”
Section: Discussionmentioning
confidence: 99%
“…Fertility may be worse in first-lactation cows in comparison with older animals (e.g. Wu et al 2012), and they experience a higher incidence of delayed resumption of ovarian cyclicity (Wathes et al 2007a). Although most older cows have achieved mature body size, they also have a greater capacity for milk production.…”
Section: Age-related Influences On Fertilitymentioning
confidence: 99%
“…This is particularly critical in systems based on a seasonal calving pattern and is still economically beneficial in all-year calving herds. In reality, however, typical calving intervals in many countries are over 400 days, and approximately 20% of cows are culled in each lactation, with failure to conceive the main reason (Brickell and Wathes 2011;Wu et al 2012). There is a widespread acceptance that the fertility of modern cows is poor and needs to be improved in future by: (1) altering the genetic breeding goals to include non-production traits (Berry et al 2003); and (2) improving management, in particular through better nutrition (Beever 2006).…”
Section: Introductionmentioning
confidence: 99%